Ferroresonance Signal Analysis with Wavelet Transform on 500 kV Transmission Lines Capacitive Voltage Transformers - I Gusti Ngurah Satriyadi Hernanda; I Made Yulistya Negara; Adi Soeprijanto; Dimas Anton Asfani; Mochammad Wahyudi; Surya Dwi Kisdarmawan; Daniar Fahmi (JAREE (Journal on Advanced Research in Electrical Engineering), 2017)
This paper deals with ferroresonance detection on an transmission line utilizing wavelet transform. The ferroresonance involving linear capacitor and non-linear inductor was triggered by the disturbances of power system, such as lightning strike, switching operation and ground fault. The primary voltage of capacitive voltage divider (CVT) was observed as response of the triggered ferroresonance. The voltage signal was processed using wavelet daubechies (db5) until 9 levels. The cyclic cumulative energy for each condition was then calculated and compared. The result shows that the cyclic cumulative energy ratio and duration of period of cumulative energy deviation can be used as ferroresonance detection parameters.Keywords: ferroresonance; capacitive voltage divider, wavelet transform